The Social Health Promotion of Elderly in Saluang Subdistrict Administative Organization, Mae Rim District, Chiang Mai Province - Jaitae, Samart; Kaewdang, Kanchunya; Deethae, Aomhatai (Journal of Liberal Arts Prince of Songkla University, 2019)
The purpose of this research was to study the social health promotion and synthesize guidelines for social health promotion of elderly. The number of sample size was 236 households and 27 stakeholders in the area of Saluang Subdistrict Administative Organization, Mae Rim District, Chiang Mai Province. A questionnaire was used as a quantitative instrument to collect data. In-depth semi-structure interview and focus group discussion were used as a qualitative instrument to collect data. Data were analyzed by descriptive statistics and content analysis. The results indicated that the physical, mental and social health were at the high level ( = 2.71± 0.47, 2.63 ± 0.94 and 2.34 ± 0.60, respectively). The stakeholders has made recommendations for the social health promotion of elderly by raising adolescents’ awareness of the value of elderly creating activities for the development of second occupation.